Design, synthesis, and in vitro, in vivo, and in silico evaluation of novel substituted 1,3,4-thiadiazole derivatives as anticonvulsant agents - Tulika Anthwal; Swati Pant; Preeti Rana; Sumitra Nain (Frontiers in Chemistry)
In the present study, a library of ten novel substituted 1,3,4‐thiadiazole derivatives were designed and synthesized using an appropriate synthetic route. The characterization of the synthesized compounds was performed by FT-IR and NMR (1H and 13C) spectroscopy. The synthesized compounds were assayed for in vitro human carbonic anhydrase (CA) inhibition against two isoforms II and IX. The neurotoxicity of the synthesized derivatives was also evaluated using the rotarod test, along with their in vivo anticonvulsant activity, which was determined using the maximal electroshock seizure (MES) and subcutaneous pentylenetetrazole (sc-PTZ) methods. Although all the compounds showed good CA inhibition and anticonvulsant activity, two compounds 6d and 7d showed the highest CA inhibition and anticonvulsant activity in both the isoforms and tested methods compared to the standard drugs (sodium valproate and acetazolamide), without any sign of neurotoxicity observed at the highest dose (300 mg/kg). Similarly, the standard drugs also displayed no neurotoxicity at the highest dose (300 mg/kg). Furthermore, the potent compounds (6d and 7d) were evaluated for the biochemical parameters, such as lipid peroxidation, nitrite oxide, reduced glutathione, superoxide dismutase, and total antioxidant capacity, and the GABA level was also determined. Finally, compound 6d was docked against CA-II and CA-IX (PDB-ID-5SZ5 and 5AML) receptors. The study concluded that the compounds 6d and 7d can be considered potent anticonvulsant agents for future research.